Standardizing the Cardiac Radioablation Targeting Workflow: Enabling Semi-Automated Angulation and Segmentation of the Heart According to the American Heart Association Segmented Model - Martijn H. van der Ree, MD; Jorrit Visser, PhD; R. Nils Planken, MD, PhD; Edith M.T. Dieleman, MD; S. Matthijs Boekholdt, MD, PhD; Brian V. Balgobind, MD, PhD; Pieter G. Postema, MD, PhD (Advances in Radiation Oncology, 2022)
Purpose: Cardiac radioablation has evolved as a potential treatment modality for therapy-refractory ventricular tachycardia. To standardize cardiac radioablation treatments, promote accurate communication and target identification, and to assess toxicity, robust, and reproducible methods for angulation and cardiac segmentation are paramount. In this study, we developed and evaluated a tool for semiautomated angulation and segmentation according to the American Heart Association 17-segment model. Methods and Materials: The semiautomated angulation and segmentation of the planning-computed tomography (CT) was based on an in-house developed tool requiring placement of only 4 point-markers and a rotation matrix. For angulation, 2 markers defining the cardiac long-axis were placed: at the cardiac apex and at the center of the mitral valve. A rotation matrix was derived that angulates the CT volume, resulting in the cardiac short axis. Segmentation was subsequently performed based on marking the 2 left ventricular hinge points. To evaluate reproducibility, 5 observers independently placed markers in planning CTs of 6 patients. Results: The root mean square of the standard deviation for the angulation and segmentation marker positions were ≤0.5 cm. The 17 segments were subsequently generated and compared between the observers resulting in a median Dice coefficient of 0.8 (interquartile range: 0.70-0.87) and a median of the mean Hausdorff distance of 0.09 cm (interquartile range: 0.05-0.17). The interquartile ranges of Euler angles α and β, determined by the angulation markers, was less than 3 degrees for all patients except one. For the γ angle, determined by the hinge point markers, the interquartile range was up to 12 degrees. Conclusions: In this study a method for semiautomatic angulation and segmentation of the heart for cardiac radioablation according to the American Heart Association Segmented Model is presented and evaluated. Based on our results we believe that the segmentation is reproducible and that it can be used to promote communication between radiation oncology and cardiology, enables cardiology-oriented targeting and permits focused toxicity evaluations.